HR Practices, Overall Satisfaction and Employee Loyalty: Does Corporate Social Responsibility Matter in Mining firms of Indonesia? - Saengchai, Sakapas; Siriattakul, Parinya; Jermsittiparser, Kittisak (International Journal of Psychosocial Rehabilitation, 2019)
The main objective of the current study is to investigate the relationship between HR practices, overall satisfaction, employee loyalty, and Corporate Social Responsibility in the mining firms of Indonesia. The overall satisfaction has examined as the mediator and the Corporate Social Responsibility as a moderator. The purpose of this paper is to examine training & development, compensation and working environment as the independent variable leading to employee loyalty. In this relationship, employee satisfaction is acting as the mediator, and Corporate Social Responsibility activities are taken as the moderating variable between satisfaction and loyalty SEM-PLS is applied mostly because of its robustness to carry out simultaneous testing of multiple relationships. The data is collected from the employees working in the mining industry of Indonesia. The findings of the study have argued that the Human resource department of any organization treats training and development of employees as the function related to organizational activity with the aim of improving the performance of employee and teams within the organization. Basically, training and development is the try of the organization to improve the future or current performance by enhancing the ability of employees through learning by changing the attitude and improving the knowledge and skills. The findings of the study are among the pioneering studies on the issue